Successful Education Reform : Lessons from Poland - Mahfooz, Sara Bin; Hovde, Kate (World Bank, Washington, DC, 2012)
Poland's education reforms have produced a large overall improvement in educational performance, as measured by results on the Organization for Economic Cooperation and Development (OECD) Program for International Student Assessment (PISA). Before 1999, primary school in Poland was 8 years, followed by tracking into vocational or academic programs. Now, the primary cycle has been changed to six years, followed by three years of comprehensive lower secondary school or gymnasium for all students, before a vocational tracking decision is made. Increased hours of instruction and delayed tracking of students into the vocational education stream were the most important factors in the improvement of test scores. In 2000, only one percent of polish students received more than four hours of language class, while in 2006, 76 percent of students received more than four hours of language class.